2019
DOI: 10.1186/s43019-019-0011-5
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary diagnosis of medial meniscus posterior root tears using the Rosenberg radiographic view

Abstract: Purpose: To verify the effectiveness of detecting medial meniscus posterior root tears (MMPRTs) using weightbearing posterior-anterior (PA) radiographs. Materials and methods: Twenty-three patients were diagnosed with an MMPRT using magnetic resonance imaging (Group A), with 23 matched individuals forming the control group (Group B). The distance between medial tibial eminence and the lateral edge of the medial femoral condyle (MTE-MFC distance) and medial joint space (MJS) width were measured on weight-bearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 35 publications
(36 reference statements)
1
19
0
Order By: Relevance
“…Medial meniscus posterior root tears (MMPRTs) are defined as an avulsion injury or radial tear occurring in the posterior bony attachment. 3,18,21 Detachment of the posterior root completely disrupts the continuity of the circumferential fibers, leading to loss of hoop tension, loss of load sharing ability, and unacceptable peak pressures. Biomechanical studies have shown that MMPRT has the same consequences as a total meniscectomy and that the pathological loads lead to degenerative arthritis.…”
mentioning
confidence: 99%
“…Medial meniscus posterior root tears (MMPRTs) are defined as an avulsion injury or radial tear occurring in the posterior bony attachment. 3,18,21 Detachment of the posterior root completely disrupts the continuity of the circumferential fibers, leading to loss of hoop tension, loss of load sharing ability, and unacceptable peak pressures. Biomechanical studies have shown that MMPRT has the same consequences as a total meniscectomy and that the pathological loads lead to degenerative arthritis.…”
mentioning
confidence: 99%
“…In the case of an MMPRT, MM extrudes medially and posteriorly [12,23]. Therefore, medial and posterior buttress function is lost even if the anterior and posterior cruciate ligaments remain intact and the femur and tibia are subluxated with knee flexion [3,22]. With this in mind, the changes in cartilage damage in the femur and tibia in the anteroposterior and mediolateral directions were evaluated; a high meniscus score at the time of second-look arthroscopy, at 1 year after MMPRT surgery, should indicate the restoration of lost medial and posterior buttress function.…”
Section: Discussionmentioning
confidence: 99%
“…The MFC was divided into nine areas and the MTP was divided into five areas (Figures 1a, e). Cartilage damage was documented in detail at the time of primary surgery and second-look arthroscopic examination [22]. Subsequently, the MFC was divided into six zones (A-F) (Figures 1b, c): the anterior, central, posterior, medial, central, and lateral zones; the MTP was divided into two zones (G and H) (Figures 1f, g): the anterior to posterior and the medial to lateral zones.…”
Section: Evaluation Of Medial Compartment Cartilage Damagementioning
confidence: 99%
“…Several characteristic MRI findings have been reported to detect MMPRT. In coronal images, giraffe neck sign and cleft/truncation sign (vertical linear defect) are useful to diagnose MMPRT [ 4 8 ]. In sagittal images, a ghost (or white meniscus) sign that shows a disappearance of the MM posterior root/horn on some slices can diagnose MMPRT with high sensitivity.…”
Section: Introductionmentioning
confidence: 99%